High levels of DJ‐1 protein and isoelectric point 6.3 isoform in sera of breast cancer patients. Issue 7 (6th May 2015) - Kawate, Takahiko; Iwaya, Keiichi; Koshikawa, Kayoko; Moriya, Tomoyuki; Yamasaki, Tamio; Hasegawa, Sho; Kaise, Hiroshi; Fujita, Tomoyuki; Matsuo, Hirotaka; Nakamura, Takahiro; Ishikawa, Takashi; Hiroi, Sadayuki; et al.
<x xml:space="preserve">Abstract</x> In patients with cancer and Parkinson's disease, the DJ‐1 protein may be secreted into the serum during the impaired response of the underlying cell‐protective mechanisms. In order to determine the clinical significance of DJ‐1 protein in the sera of breast cancer patients, we examined blood samples from a breast cancer group (n = 180) and a non‐cancerous control group (n = 300). Higher levels of DJ‐1 were detected in the breast cancer group (mean level, 42.7 ng/mL) than the control group (28.3 ng/mL) by ELISA (P = 0.019). Higher DJ‐1 levels were significantly associated with advanced clinical grade, according to the TNM classification, negative hormone receptor status, and high Ki‐67 labeling index, of biopsied materials; samples showed low DJ‐1 protein expression despite upregulated DJ‐1 mRNA. DJ‐1 isoforms could be detected clearly in 17 blood samples (from 11 breast cancer patients, and 6 non‐cancerous controls) by 2‐D gel electrophoresis and immunoblot analysis. The isoform at the pI of 6.3 showed the highest intensity in all 11 cancer cases. Conversely, in the 6 non‐cancerous cases, isoforms other than the pI 6.3 isoform were highly expressed, and there was a significant difference in the isoform pattern between breast cancer cases and controls (P = 0.00025). These data indicate that high levels of DJ‐1, probably of isoform at pI 6.3, is a candidate serum marker of breast cancer.